The Effect of Intellectual Capital on Firm Performance: A State of the Art - Jikhan, Fat'Chatus Chanifa; Muftiadi, Anang; Alexandri, Mohammad Benny (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 2 (2023), 2023)
This research scrutinized the impact of intellectual capital on firm performance, identifying pertinent scientific publications using a systematic literature review. The findings reveal an upward annual trend in empirical research concerning the effect of intellectual capital on company performance. Over the past decade, Indonesia has emerged as a dominant contributor to this research. While nine dimensions of intellectual capital have been pinpointed, three specific dimensions are predominantly studied. Research on Small and Medium Enterprises (SMEs) has been a focal point over the last ten years. Additionally, Andreeva & Garanina’s 2016 study stands out as a frequently cited work. Furthermore, the conceptualization of intellectual capital and the evolution of its dimensions were significantly influenced by foundational research. These insights, distilled from the analysis of 35 empirical research articles, enrich the ongoing discourse on intellectual capital and its connection to firm performance. It's noteworthy that human, structural, and relational capital have emerged as dominant dimensions of intellectual capital. This study underscores the importance and prevalence of intellectual capital concepts that various firms leverage to bolster their performance. Keywords: intellectual capital, firm performance, systematic review